Resveratrol alleviates ethanol-induced hormonal and metabolic disturbances in the rat - Szkudelska, K; Deniziak, M; Roś, P; Gwóźdź, K; Szkudelski, T (Physiological research, 2017)
Resveratrol is a polyphenol found in different plant species and having numerous health-promoting properties in animals and humans. However, its protective action against deleterious effects of ethanol is poorly elucidated. In the present study, the influence of resveratrol (10 mg/kg/day) on some hormones and metabolic parameters was determined in rats ingesting 10 % ethanol solution for two weeks. Blood levels of insulin, glucagon and adiponectin were affected by ethanol, however, resveratrol partially ameliorated these changes. Moreover, in ethanol drinking rats, liver lipid accumulation was increased, whereas resveratrol was capable of reducing liver lipid content, probably due to decrease in fatty acid synthesis. Resveratrol decreased also blood levels of triglycerides and free fatty acids and reduced gamma-glutamyl transferase activity in animals ingesting ethanol. These results show that resveratrol, already at low dose, alleviates hormonal and metabolic changes induced by ethanol in the rat and may be useful in preventing and treating some consequences of alcohol consumption.
Keywords: játra; metabolismus lipidů; glukagon; Triglycerides; Resveratrol; kyseliny mastné neesterifikované; resveratrol; stilbeny; Lipid Metabolism; ethanol; krysa rodu Rattus; zvířata; potkani Wistar; triglyceridy; Liver; Rats, Wistar; Stilbenes; Male; Adiponectin; Insulin; adiponektin; Fatty Acids, Nonesterified; Rats; Animals; Ethanol; mužské pohlaví; inzulin; Glucagon